Iowa field reports contributed by Stephen J. Dinsmore, fall 1997 - Dinsmore, Stephen J.et al (1997)
Fall report of birds and locations contributed by Stephen J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed